International Student Mobility to Canada and New Zealand: “Edugration” or “Transience”? - King, Conrad; Gomes, Catherine; Shannon, William; Lu, Ruonan (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
Policymakers in some key Western international education hubs assume that international student mobility (ISM) is based on aspirations for permanent migration, particularly if those students come from the Global South. The concept of edugration—an amalgam of education and immigration—has become influential in both policy and research. This paper examines student motivations for ISM in Canada and New Zealand using a mixed methods approach of online surveys and focus group interviews, collecting data from 396 international student participants (Canada: n = 244; New Zealand: n = 152). The results show a nuanced picture, highlighting that many students view international study as a transient experience rather than one that facilitates permanent migration. The paper also discusses the extent to which a desire to attract potential migrants is reflected in policies related to ISM in the two countries, and the potential implications of the findings for these policies.